2021
DOI: 10.1080/21655979.2021.1972200
|View full text |Cite
|
Sign up to set email alerts
|

Integrated weighted gene co-expression network analysis uncovers STAT1(signal transducer and activator of transcription 1) and IFI44L (interferon-induced protein 44-like) as key genes in pulmonary arterial hypertension

Abstract: 2021) Integrated weighted gene co-expression network analysis uncovers STAT1(signal transducer and activator of transcription 1) and IFI44L (interferon-induced protein 44-like) as key genes in pulmonary arterial hypertension,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Apo lipoprotein E (APOE) ( Rao et al, 2022 ), Angiotensinogen II Type 1 Receptor (AGTR1) ( Wulandari et al, 2018 ), Angiotensin-converting enzyme (ACE) ( Ya et al, 2019 ), methylenetetrahydrofolate reductase (MTHFR) ( Garakanidze et al, 2018 ), endothelin1 (EDN1) ( Yang et al, 2021 ), ring finger protein 213 (RNF213) ( Suzuki et al, 2018 ), Alpha-Adducin 1 (ADD1) ( Yermolenko et al, 2021 ), tumor necrosis factor (TNF) ( Khlynova et al, 2020 ) and T-box transcription factor 2 (TBX2) ( Abramova et al, 2020 ) involve in the AH process and the overexpression of them can cause amplification in AH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apo lipoprotein E (APOE) ( Rao et al, 2022 ), Angiotensinogen II Type 1 Receptor (AGTR1) ( Wulandari et al, 2018 ), Angiotensin-converting enzyme (ACE) ( Ya et al, 2019 ), methylenetetrahydrofolate reductase (MTHFR) ( Garakanidze et al, 2018 ), endothelin1 (EDN1) ( Yang et al, 2021 ), ring finger protein 213 (RNF213) ( Suzuki et al, 2018 ), Alpha-Adducin 1 (ADD1) ( Yermolenko et al, 2021 ), tumor necrosis factor (TNF) ( Khlynova et al, 2020 ) and T-box transcription factor 2 (TBX2) ( Abramova et al, 2020 ) involve in the AH process and the overexpression of them can cause amplification in AH.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-663 demonstrated the most tendency to NOS2 which ameliorates AH. on the other side, early studies have shown that this microRNA decreases arterial blood pressure in patients as this microRNA has exerted suppressive effects on AH by inhibition of TGF-β and subsequently, oppression of TGF-β1/smad2/3 signaling, vascular remodeling (Zhu et al, 2020;Li et al, 2021). Furthermore, in a study performed on 91 Caucasian participants from Eastern Siberia, it was found out that rs2779249 and rs229718 polymorphism of the NOS2 gene were associated with AH (Alyabyeva et al, 2023).…”
Section: Mir-663 Has the Most Binding Affinity To Nitric Oxide Syntha...mentioning
confidence: 99%
“…A previous study found that LMNA (lamin A/C) [85], SLC11A2 [163], CRTC2 [164], TBK1 [165], GRN (granulin precursor) [166], CTSD (cathepsin D) [167], STARD10 [168], PGRMC1 [169], TFE3 [170], POR (cytochrome p450 oxidoreductase) [171], SESN1 [172], IL15 [173], PIK3R1 [134], OSM (oncostatin M) [98], SOCS3 [174], USP21 [100], GLUL (glutamate-ammonia ligase) [175], IL1R1 [176], TP53 [177], PPM1A [178], CTBP1 [179], DNAJC3 [180], ATP6 [181], DDX21 [182], COX2 [183], RACK1 [184], ND1 [158], CCND2 [185] and COX1 [186] are positively correlated with type 2 diabetes mellitus, suggesting its potential as a biomarker for type 2 diabetes mellitus. LMNA (lamin A/C) [187], PFKFB3 [188], TRAF2 [189], ADORA2B [190], ACADS (acyl-CoA dehydrogenase short chain) [191], IRF7 [192], ASL (argininosuccinatelyase) [193], IL15 [194], PIK3R1 [195], OSM (oncostatin M) [196], SOCS3 [197], CHD9 [198], IFI44L [199], GNLY (granulysin) [200], FLNB (filamin B) [201], IL1R1 [202], SETD3 [203], TP53 [204], BRD4 [205], COX2 [206], HSP90AB1 [207], SLC7A1 [208], ND2 [209] and COX1 [210] have been reported to be associated with hypertension. LMNA (lamin A/C) [211], INPP5K [212], SCYL1 [213], AKR7A2 [214], TRAF2 [215], SLC11A2 [216], NEU1 [217], SNAP29 [218], DUSP22 [219], P2RX4 [220], ADORA2B [221], NAXD (NAD(P)HX dehydratase) [222], FEZ1 [223], TBK1 [224], GRN (granulin precursor) [225], ATG4D [226], CTSD (cathepsin D) [227], PPP2R5D […”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [578], Park et al [579], Yang et al [580], Yu et al [581] and Forero-Delgadillo et al [582] mentioned that hsa-mir-21-5p, STAT3, STAT1, GATA2 and PAX2 were related to other kidney diseases. Studies have indicated that hsa-mir-21-5p [583], STAT3 [584], STAT1 [585] and GATA2 [586] plays a substantial role in hypertension. Ortiz-Dosal et al [587], Su et al [588] and Cox et al [589] demonstrated that the altered expression of hsa-mir-21-5p, STAT3 and STAT1 are associated with progression of obesity.…”
Section: Discussionmentioning
confidence: 99%